Acetylcysteine Treatment of Acetaminophen Overdose: Foundational and Clinical Development - Barry H. Rumack (Livers, 2025)
N-acetyl para-aminophenol was suggested as a safer alternative to other drugs on the market for pain and fever in 1948. It was given the generic name “acetaminophen” in 1951 and the trade name “Tylenol” when it was put on the market in the USA in 1955 as a prescription drug to treat pediatric fever. It also received the generic name “paracetamol” in the UK where it was initially marketed in 1956 under the name “Panadol.” Toxicity from overdose of acetaminophen was reported in 1966. Research at the US National Institutes of Health uncovered the mechanisms of toxicity and proposed a treatment in a foundational series of papers in 1973 and 1974. A nomogram was developed in 1973 and published in 1975 to guide estimation of patient risk of hepatic toxicity. Rapid development followed utilizing acetylcysteine given both orally and intravenously. Various protocols and methods of administration have been employed over time with the primary use today of acetylcysteine intravenously as the therapeutic method. The nomogram has been revised over time to the current version, published in 2023, which allows stratification of patients to a high-risk group over 300 mg/L at 4 h and standard risk above 150 mg/L at 4 h, except in the UK where the standard risk is defined very conservatively with a line above 100 mg/L at 4 h. Adjunct therapy with fomepizole in patients with massive ingestions, delay until arrival in a health care facility or renal injury has been proposed. The mortality rate with treatment has been substantially reduced and recovery from hepatic injury is achieved in almost all patients.